Способ получения гексафторидов актинидных элементов и устройство для его осуществления - Гаврилов П. М. Петр Михайлович; Ревенко Ю. А. Юрий Александрович; Бондин В. В. Владимир Викторович; Бычков С. И. Сергей Иванович; Лапшин Б. М. Борис Михайлович; Алексеенко В. Н. Владимир Николаевич
опубл. 20.07.10